2019
DOI: 10.31578/jebs.v4i2.179
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Metacognitive Technique for Enhancing the Writing Skills of Arab EEFL Students

Abstract: One of the most problematic areas for foreign language learning is writing. Writing is the most complicated and complex aspect of the language system. This study aimed to investigate the kind of metacognitive strategies EFL students used before and after metacognitive strategy training and the effect of the changes observed. It also aimed to examine the influence of other external factors (L1 transfer, motivation, anxiety) on EFL students' performance when instructed to use metacognitive strategies. The subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Also, characteristics of the student population might have influenced the results obtained; similarly, these could not be predicted or monitored. Relevant studies that indicated that the use of games had a significant effect on students' language acquisition used students from the same school or classes with the same teacher (Al-Jarrah, Talafhah & Al-Jarrah, 2019). In other studies, the same group of students acted both as an experimental and as a control group (Omar & Said, 2019;Stavy, Subon & Unin, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Also, characteristics of the student population might have influenced the results obtained; similarly, these could not be predicted or monitored. Relevant studies that indicated that the use of games had a significant effect on students' language acquisition used students from the same school or classes with the same teacher (Al-Jarrah, Talafhah & Al-Jarrah, 2019). In other studies, the same group of students acted both as an experimental and as a control group (Omar & Said, 2019;Stavy, Subon & Unin, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Writing skills are an essential part of English as a Foreign Language (EFL) study since they not only act as a medium of communication but also play an essential role in a student's professional and Setya Resmini 1 , Gartika Pandu Bhuana 2 , Siska Rizkiani 3 , Angga Maulana 4 EFL Students' Strategies in the Process of Writing 2 academic achievement (Ghafar & Mohamedamin, 2022). Understanding the strategies used by EFL students in the writing process is critical for both educators and researchers, as it offers insight into the metacognitive and cognitive functions involved in this complex job (Talafhah et al, 2019). The relationship between writing and the writing process is inherent and mutually beneficial, forming a dynamic interaction of idea and expression.…”
Section: Introductionmentioning
confidence: 99%
“…These skills require at least basic higher order thinking skills [10]. The writing involves setting a goal, studying the composition of the text, oriented to the reader, the subsequent verification of the correctness of the presentation and communication of thoughts and grammatical correctness of the presentation [11,12]. Therefore, researchers in the teaching of the Arabic language suggest the use of language skills as the primary stage of teaching.…”
Section: Introductionmentioning
confidence: 99%